Моделювання джерел живлення для заряду ємнісних накопичувачів енергії - Тесленко, О. С. (ХНУРЕ, 2024)
The paper discusses options for constructing high-voltage power supplies for charging capacitive energy storage devices. Modeling of various variants of converter units and analysis of their characteristics were carried out. Recommendations on the construction structure and elements of chargers are presented
Keywords: джерело живлення; ємнісний накопичувач енергії